Integrating financial inclusion and digital technology to foster inclusive economic development in Indonesia - Anindyntha, Firdha Aksari; Rusdianasari, Fitri (Universitas Muhammadiyah Yogyakarta, 2026)
Equitable economic development is reflected in sustainable economic growth and equitable income distribution. The financial sector plays an important role in supporting inclusive development, which prioritizes financial inclusion among its main policy objectives. Despite the banking sector's digital transformation in Indonesia, regional disparities in financial access and digital penetration persist, particularly in remote areas, thereby hindering the achievement of inclusive development. This study aims to analyze the role of financial inclusion and digital innovation in promoting equitable economic development, as reflected in economic growth and income inequality. This study employs a Fixed Effects Model (FEM) for panel data regression across 33 provinces in Indonesia during 2018-2023 periods. The FEM is used to control for unobserved regional heterogeneity and to ensure more consistent and unbiased estimation. Our research results show that economic growth is positively affected by financial inclusion, particularly through the availability of bank branches and lending. In addition, the adoption of digital technology also significantly contributes to driving economic growth. Furthermore, our findings reveal that the synergy between digital innovation and financial services effectively narrows the income gap across provinces. This study makes a significant scientific contribution by demonstrating that digital innovation serves not only as a technological tool but also as a key factor in enhancing the effectiveness of financial inclusion in driving economic growth and reducing income inequality. These findings provide empirical policy guidance for the development of a digital financial ecosystem to promote more inclusive and equitable economic development in Indonesia.